2017
DOI: 10.1177/0146167216688204
|View full text |Cite
|
Sign up to set email alerts
|

On the Attitudinal Consequences of Being Mindful

Abstract: A series of studies examined whether mindfulness is associated with the experience of attitudinal ambivalence. Studies 1A and 1B found that mindful individuals expressed greater comfort holding ambivalent views and reported feeling ambivalent less often.More mindful individuals also responded more positively to feelings of uncertainty (as assessed in Study 1B). Study 2 replicated these effects and demonstrated that mindful individuals had lower objective and subjective ambivalence across a range of attitude ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 47 publications
(84 reference statements)
3
16
0
Order By: Relevance
“…Furthermore, studies on mindful attention ( Haddock et al, 2017 ) describe that high attention is required for self-insight but place less focus on the learning and discovery qualities of interest here. We furthermore differentiate self-insight from insight about events, more broadly.…”
Section: High Quality Listening Fosters Self-insightmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studies on mindful attention ( Haddock et al, 2017 ) describe that high attention is required for self-insight but place less focus on the learning and discovery qualities of interest here. We furthermore differentiate self-insight from insight about events, more broadly.…”
Section: High Quality Listening Fosters Self-insightmentioning
confidence: 99%
“…Indirect evidence comes from research on mindfulness, which is conceptualized as non-judgmental awareness of the present ( Kabat-Zinn, 2015 ). Specifically, when individuals are mindfully aware of conflictual affect and self-relevant information they show more emotional differentiation ( Hill & Updegraff, 2012 ), better self-regulation ( Erbas et al, 2014 ), and respond more positively to situations of uncertainty ( Haddock et al, 2017 ). Mindful attention has also been linked to changing stereotypes and prejudice (e.g., Djikic et al, 2008 ; Lillis & Hayes, 2007 ; Lueke & Gibson, 2015 ).…”
Section: High Quality Listening During Difficult Conversationsmentioning
confidence: 99%
“…We first tried to replicate the past research showing that mindfulness negatively predicts OA and SA (Haddock et al, 2017). To do this, we used cross-classified multilevel models as described above.…”
Section: Resultsmentioning
confidence: 99%
“…Building off of the idea that mindfulness can reduce inconsistencies (see also Crane et al, 2008), Haddock et al (2017) showed that as mindfulness increased, people reported being more comfortable holding ambivalent attitudes and reported experiencing ambivalent attitudes less often. They also showed that mindfulness predicted less OA and SA across a number of topics (see also Dummel, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…First and Social Psychological Bulletin | 2569-653X https://doi.org/10.5964/spb.v13i3.27574 foremost, these would be factors that impact source confusability. For example, chronic ambivalence (Haddock, Foad, Windsor-Shellard, Dummel, & Adarves-Yorno, 2017) involves the regular experience of both positive and negative affect toward a variety of objects. It may be that chronically ambivalent individuals are more likely to misattribute any experienced affect.…”
Section: Does the Model Predict Any Individual Differences At Any Stamentioning
confidence: 99%